A Study on Connecting Customers through Presence of Regional Brands in Food Retailing - John, S. Franklin; Ramakrishnan, Sheeja (International Journal of Social Sciences and Management, 2017)
The Indian retail industry is the fifth largest in the world. Comprising of organized and unorganized sectors, India retail industry is one of the fastest growing industries in India, especially over the last few years. Though initially, the retail industry in India was mostly unorganized, however with the change of tastes and preferences of the consumers, the industry is getting more popular these days and getting organized as well. With growing market demand, the industry is expected to grow at a pace of 25-30% annually. The India retail industry is expected to grow from Rs. 35,000 crore in 2004-05 to Rs. 109,000 crore by the year 2010. In 2007, the retail trade in India had a share of 8-10% in the GDP (Gross Domestic Product) of the country. The study examines the role of regional brands in connecting customers in food retailing. Private labels or store brands are on escalating journey for growth in last few years in Indian market. The growth of private label brands (PLBs) is quite impressive in food and grocery segment, in spite of presence of leading national manufacturers brands in most of the categories. Though, initially PLBs were considered as cheap alternatives and therefore visible in copycat and generic categories, today they are a part of well defined retail mix strategy, are developed in value innovators and premium categories for profit maximization and customer loyalty. Int. J. Soc. Sc. Manage. Vol. 4, Issue-1: 55-59